Armoring chimeric antigen receptor (CAR) T cells as micropharmacies for cancer therapy - C. Carcopino; E. Erdogan; M. Henrich; S. Kobold (Immuno-Oncology and Technology)
Chimeric antigen receptor (CAR)-T-cell therapy has emerged as a powerful weapon in the fight against cancer. However, its efficacy is often hindered by challenges such as limited tumor penetration, antigen escape, and immune suppression within the tumor microenvironment. This review explores the potential of armored CAR-T cells, or ‘micropharmacies’, in overcoming these obstacles and enhancing the therapeutic outcomes of adoptive T-cell (ATC) therapy. We delve into the engineering strategies behind these advanced therapies and the mechanisms through which they improve CAR-T-cell efficacy. Additionally, we discuss the latest advancements and research findings in the field, providing a comprehensive understanding of the role of armored CAR-T cells in cancer treatment. Ultimately, this review highlights the promising future of integrating micropharmacies into ATC therapy, paving the way for more effective and targeted cancer treatments.